Judging inequality : state supreme courts and the inequality crisis - Gibson, James L., 1951-; Nelson, Michael J., 1986- (Russell Sage Foundation, 2021)
"This book investigates the policies made by state high courts that pertain to the seemingly inexorable rise of political, legal, economic, and social inequality in the United States, using data assembled by the authors on the equality-relevant decisions made by the state supreme courts from 1990 to 2015"--